(untitled) (TAMADDUN NURI JURNALI, 2025)
This article sheds light on the essence of the concept of patriotism. To love one’s homeland, one needs tolerance. Such tolerance prepares a person for true courage, and if necessary, to sacrifice one’s life. Today, spirituality serves as the most effective and powerful weapon in educating all-round excellent internal affairs officers in the spirit of patriotism.